Modern financial techniques, derivatives, and law - Hudson, Alastair; Southern Methodist University. Institute of International Banking and Finance (The Hague ; Boston : Kluwer Law International, 2000)
This work examines both the UK and international regulation, as well as the case law and legislation affecting a wide spectrum of modern financial techniques.
Includes bibliographical references and index.
rpm 09/05/13
Loans
Keywords: Financial instruments; Derivative securities -- Law and legislation